Maternal sleep-disordered breathing and the risk of delivering small for gestational age infants: a prospective cohort study. Issue 8 (15th April 2016) - Pamidi, Sushmita; Marc, Isabelle; Simoneau, Gabrielle; Lavigne, Lorraine; Olha, Allen; Benedetti, Andrea; Sériès, Frédéric; Fraser, William; Audibert, François; Bujold, Emmanuel; Gagnon, Robert; Schwartzman, Kevin; et al.
Abstract : Objective: It is unclear whether objectively measured maternal sleep-disordered breathing (SDB) leads to poor fetal outcomes. In this study, we prospectively assessed whether polysomnography-based diagnosis of SDB in the third trimester is associated with the delivery of small for gestational age (SGA) infants. Study design: Participants were recruited from a multicentre pregnancy cohort study. Eligible participants were evaluated for SDB based on symptoms (snoring and/or witnessed apnoeas assessed using the Pittsburgh Sleep Quality Index questionnaire) and in-home complete polysomnography in the third trimester. SGA was defined as <10th centile using customised birthweight centiles adjusted for maternal parity, prepregnancy body mass index (BMI), ethnicity, gestational age and infant sex. Results: Of the 234 pregnant participants who completed a sleep study, 82% were Caucasian, with mean (SD) age of 31 (4.3) years and a prepregnancy BMI of 23 (4) kg/m 2 . The delivery of SGA infants occurred in 27 (12%) of the study participants. The symptoms of SDB had poor overall sensitivity and specificity for diagnosing SDB identified by polysomnography. Symptoms of SDB in the third trimester demonstrated a potential association with delivering an SGA infant, however this did not reach statistical significance (OR 2.36 (95% CI 0.85 to 6.54, p=0.10)). However, the odds of delivering an SGA infant were significantly increased with polysomnography-based diagnosis of maternal SDB (using apnoea-hypopnoea index cut-off of 10, OR 2.65 (95% CI 1.15 to 6.10, p=0.02)). Conclusions: Objectively measured SDB in the third trimester is significantly associated with the delivery of SGA infants.